Cronogeomorfologia do relevo da cidade de Marília através do método de traços de fissão - MTF - Santos, Caio Augusto Marques dos [UNESP] (2014)
The Marília Residual Plateau is a morfosculpture located in Paulista Western Plateau and in morfostructure of the Paraná Sedimentary Basin. It has as rock substratum the sandstones of Marília Formation (Bauru Group - Late Cretaceous). In order to check the role and importance of tectonics to its genesis and evolution, it was done the dating of 110 grains of zircon and 59 of apatite by Fission Track Method - MTF. This method is based on thermal-chronological analyzes, grounded on the quantitative study of disturbances at the crystal lattice of these minerals caused by the spontaneous fission of the nucleus of 238U isotope, which occurs along geological time. The results obtained for zircon had ages break between 640 to 70 Ma. In apatite the variation was from 489 to 71 Ma. These large ranges of age were attributed to several origins of source rocks that provide the sediments to rock substratum of plateau. By analyzing the age spectrum of these two minerals, they were grouped into three sets, associated with thermo-tectonic events: ages over 470 Ma - brasiliano...